A constituição do meio técnico-científico em Goiás: relações de trabalho e luta de classes no setor sucro-energético - Santos, Lucas Maia dos (2014)
This thesis aims at analyzing the process of constitution of the technical and scientific environment in Goiás. At first, it is important to emphasize the way in which the term is employed. Although there are similarities with what Milton Santos has elaborated, this study also presents itself distant from such elaboration. Through this research, one can state that the technical and scientific environment is actually the instauration of a geographical environment (technical) which is adequate to capitalist productions. In order to demonstrate so, it was necessary to bring about other concepts, such as capital accumulation, which allows us to fully understand, within the history of Capitalism, the different phases of the institution of the technical and scientific environment. In this process of periodization to outline the capitalist society, as a whole, and its process of territorialization in Goiás, it was necessary to show the agrobusiness concept, owing to the fact that this was one of the segments through which a scientific and technical environment was set in Goiás. After demonstrating how such geographical environment has been consolidated in Goiás, a debate took place in order to show how it brings certain class conflicts about. To understand such class conflicts, which define the technical and scientific environment, the research focuses on the city of Quirinópolis, in a moment when one could analyze how Quirinópolis’s workers deal with their own work relations, based on the sucrenergetic sector. In order to conclude the thesis, one states that the historic tendency of capital accumulation, as it was elaborated by Karl Marx, is also confirmed in the analyses of the technical and scientific environment, that is, in the territory of the capital.